Indicators of Citizen-Centric Public Service Delivery - World Bank Group (World Bank, Washington, DC, 2018)
This report and the instruments it proposes aim at assisting public administrators in ensuring that their service delivery mechanisms respond to the needs and expectations of citizens. This document summarizes research undertaken under the set of activities dealing with citizen-centric governance indicators, that is, indicators that measure the capacity of public agencies to put the needs of citizens at the center of their service delivery mechanisms. The report is structured into five parts. Part I presents the conceptual framework that forms the backdrop for developing citizen-centric service delivery indicators and summarizes what citizen-centric service delivery entails. Part II introduces two complementary tools designed to assess the performance of public institutions and the quality of public services from the perspective of European Union citizens: a demand-side citizen survey and a supply-side self-assessment checklist for public administrators. These complementary instruments, assist public agencies identify gaps and areas for improvement in their service delivery mechanisms by gathering direct feedback regarding the experiences and perceptions of their users and by critically examining public sector efforts to fulfill the needs and expectations of citizens. The instruments are flexible, inspirational tools that provide an initial grid for administrations willing to move one step closer to their citizens. Part III describes options for customizing the instruments, which can be adapted to a variety of circumstances and service delivery types. Parts IV and V present the citizen survey and administrator checklist.